Pandangan Dunia Pengarang dalam Novel "Warisan" Karya Chairul Harun: Tinjauan Strukturalisme Genetik - Tisa Sirefina; Khairil Anwar; Hasanuddin Hasanuddin (Jurnal Elektronik WACANA ETNIK, 2018)
Novel Warisan with a Minangkabau social background that tells the story of a dispute over inheritance. In this case, the novel is analyzed by a genetic structuralism approach that analyzes the structure of the story and relates it to the social structure of the community, then reveals the author's worldview that it reflects.This study concluded that Warisan's novel by Chairul Harun reflected the worldview of the author as a member of the Minangkabau community who had changed. Changes seen in the patterns of behavior and actions of the people are no longer in line with the Minangkabau philosophy, namely Basandi Syarak Customary, Syarak Basandi Kitabullah. Changes are caused by the influence of colonialization and modernization. The world view is the collective mind, in this case the Minangkabau educated group.